Intensified conditioning containing decitabine versus standard myeloablative conditioning for adult patients with KMT2A-rearranged leukemia: a multicenter retrospective study - Hu, Zhongli; Feng, Zinan; Liu, Shiqi; He, Hai; Dong, Ying; Fan, Zhiping; Li, Yiqing; Huang, Fen; Xu, Na; Liu, Can; Zeng, Yunxin; Zhu, Ping; et al. (BMC medicine, 2024)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is recommended for patients with KMT2A-rearranged (KMT2A-r) leukemia whereas relapse remains high. We aimed to determine whether intensified conditioning containing decitabine (Dec) could reduce relapse compared with standard myeloablative conditioning in adult patients with KMT2A-r leukemia. We performed a multicenter retrospective study at seven institutions in China. Eligible patients were aged 14 years or older at transplantation, had a diagnosis of KMT2A-r leukemia, and underwent the first allo-HSCT. Standard myeloablative conditioning regimens (standard group) included BuCy (busulfan 3.2 mg/kg/day on days -7 to -4; cyclophosphamide 60 mg/kg/day on days -3 to -2) and TBI-Cy (total body irradiation 4.5 Gy/day on days -5 to -4; Cy 60 mg/kg/day on days -3 to -2). Intensified conditioning regimens containing Dec (intensified group) consisted of Dec-BuCy (Dec 20 mg/m /day on days -14 to -10; the same dose of BuCy) and Dec-TBI-Cy (Dec 20 mg/m /day on days -10 to -6; the same dose of TBI-Cy). Between April 2009 and December 2019, 218 patients were included in this study, of whom 105 were in the intensified group and 113 were in the standard group. The 3-year cumulative incidence of relapse was 17.6% and 34.5%, overall survival was 71.3% and 61.0%, disease-free survival was 70.1% and 56.0%, and non-relapse mortality was 12.3% and 9.5% in the intensified and standard groups, respectively (P = 0.001; P = 0.034; P = 0.005; P = 0.629). Subgroup analysis showed that the relapse rate of intensified conditioning was lower than that of standard conditioning in multiple subgroups, including different leukemia types, disease status at transplantation, high-risk cytogenetics and Bu-based regimens. There was no difference in regimen-related toxicity, engraftment, or graft-versus-host disease between the intensified and standard groups. These results suggest that intensified conditioning containing Dec might be a better strategy than standard myeloablative conditioning for adult patients with KMT2A-r leukemia undergoing allo-HSCT.